Manajemen Komunikasi Pemasaran Akun Preloved @Bbybranded Di Instagram - Zahra Zahidah; O. Hasbiansyah (Bandung Conference Series: Communication Management, 2024)
Abstract. In this modern era of rapid development of technology and information, people show creativity by utilizing technology, such as Instagram, as a marketing tool. The rapid growth of Instagram users in Indonesia has made it a gateway for online sales, including for @bbybranded Preloved account. This research aims to implement marketing communication management on @bbybranded with constructivism paradigm and case study approach. The results in this study show that the implementation stages include content packaging with team discussions, content research, content planner, creation, uploading content on Instagram, and evaluation with the team. Target audience management by @bbybranded involves three stages, namely uploading preloved products, monitoring consumers, and utilizing insight features on Instagram. In sales and marketing communication activities, @bbybranded faced obstacles such as content packaging, communication barriers, and constraints from the Instagram account, which were overcome with appropriate solutions. Instagram was chosen as the only social media due to its user popularity, ease of interaction, and features that support the sale of preloved products. This decision was based on the view that Instagram makes it easy to interact with followers of the @Bbybranded account and makes it easier to sell preloved products. Abstrak. Dalam era modern ini perkembangan teknologi dan informasi yang semakin pesat saat Dalam era modern, masyarakat menunjukkan kreativitas dengan memanfaatkan teknologi, seperti Instagram, sebagai alat pemasaran. Pengguna Instagram yang melesat di Indonesia membuatnya menjadi gerbang penjualan online, termasuk bagi akun Preloved @bbybranded. Penelitian ini bertujuan mengimplementasikan manajemen komunikasi pemasaran pada @bbybranded dengan paradigma konstruktivisme dan pendekatan studi kasus. Hasil dalam penelitian ini menunjukan Tahapan implementasi mencakup pengemasan konten dengan diskusi tim, riset konten, content planner, pembuatan, unggah konten di Instagram, dan evaluasi bersama tim. Pengelolaan target audience oleh @bbybranded melibatkan tiga tahap, yaitu unggah produk preloved, pemantauan konsumen, dan pemanfaatan fitur insight di Instagram. Dalam kegiatan penjualan dan komunikasi pemasaran, @bbybranded menghadapi hambatan seperti pengemasan konten, hambatan komunikasi, dan kendala dari akun Instagram, yang diatasi dengan solusi yang sesuai. Instagram dipilih sebagai satu-satunya media sosial karena popularitas pengguna, kemudahan interaksi, dan fitur yang mendukung penjualan produk preloved. Keputusan ini didasarkan pada pandangan bahwa Instagram memudahkan interaksi dengan pengikut dari akun @Bbybranded dan mempermudah penjualan produk preloved.